2022
DOI: 10.6018/sportk.538991
|View full text |Cite
|
Sign up to set email alerts
|

Management of pedagogical and sports educational institutions in Ukraine

Abstract: The educational system is an essential component and determinant of social development since education functioning quality determines and forms the intellectual potential of society. This article aimed to identify the main trends and promising areas of optimization of the managing process of pedagogical and sports educational institutions. We studied the tendencies of reforming the management process in the educational sphere and the application of modern approaches to the management of pedagogical and sports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It helps in developing communicative skills, fosters collaborative problem-solving in language-related issues, encourages interaction among learners, provides experience in peer-to-peer learning, stimulates creativity, and increases motivation and lesson pace. However, it is important to note some drawbacks of using a multimedia board, including the potential for deterioration of learners' eyesight, rapid fatigue, possible technical issues, and the necessity for teachers to invest time in preparation and acquire technical proficiency with new software (Kubitskyi et al, 2022;Iatsyshyn et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It helps in developing communicative skills, fosters collaborative problem-solving in language-related issues, encourages interaction among learners, provides experience in peer-to-peer learning, stimulates creativity, and increases motivation and lesson pace. However, it is important to note some drawbacks of using a multimedia board, including the potential for deterioration of learners' eyesight, rapid fatigue, possible technical issues, and the necessity for teachers to invest time in preparation and acquire technical proficiency with new software (Kubitskyi et al, 2022;Iatsyshyn et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the articles (Voznyuk et al, 2022;Bakhmat et al, 2022;Kasych et al, 2021) do not sufficiently define the adaptive management tools of modern institutions of higher education, taking into account the unstable external environment and risks of the financial system. Scientists (Gryshchenko et al, 2023; Kubitskyi et al, 2022) thoroughly define the tools of interaction between business, government, and educational institutions, but they do not sufficiently take into account the factors that can change communications, especially in turbulent educational markets. Scientists (Oseredchuk et al, 2022), despite the innovative tools for monitoring distance education, practically do not consider the factors that will stimulate the attraction of intellectual potential for higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific work (Kasych et al, 2021) rightly noted the need to stimulate the development of intellectual capital as a necessary factor in the development of any institution, organization or enterprise. The management tools of the pedagogical and sports educational institutions of Ukraine are described in detail in the work (Kubitskyi et al, 2022). Scientists have described in detail the innovative tools that should be used in education to increase the effectiveness of intellectual potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that there are many suggested definitions, different conceptual frameworks have also been proposed as a theoretical basis for understanding the correlation between Internet addiction and behavioral patterns, especially among students (Huys et al, 2016). It has been suggested that stress or anxiety reduction is a possible explanation for Internet addiction (Kim et al, 2016;Kubitskyi et al, 2022;Krutsevich et al, 2021). According to this theory, the motivation for the behavioral support of Internet addiction by "excessive users" is that the Internet is used as a means to reduce stress or tension (Kim et al, 2016;Dutchak et al, 2022;Kotsur et al, 2021).…”
Section: Discussionmentioning
confidence: 99%